2016
DOI: 10.1071/fp16037
|View full text |Cite
|
Sign up to set email alerts
|

Root morphological traits that determine phosphorus-acquisition efficiency and critical external phosphorus requirement in pasture species

Abstract: Annual pasture legume species can vary more than 3-fold in their critical external phosphorus (P) requirement (i.e. P required for 90% of maximum yield). In this work we investigated the link between root morphology, P acquisition and critical external P requirement among pasture species. The root morphology acclimation of five annual pasture legumes and one grass species to low soil P availability was assessed in a controlled-environment study. The critical external P requirement of the species was low (Dacty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
64
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 31 publications
6
64
1
2
Order By: Relevance
“…The lack of the correlation between shoot P content and root hair length in the present study might be due to the relatively short root hair lengths of all chickpea genotypes (only 0.30–0.46 mm) compared with other plant species; for example, root hair lengths were 0.35–1.19 mm for five perennial pasture grass species grown in three low‐P acid soils (Haling et al ., ) and 0.50–0.75 mm for Dactylis glomerata , Ornithopus spp. and Biserrula pelecinus (Haling et al ., ). The findings of Haling et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The lack of the correlation between shoot P content and root hair length in the present study might be due to the relatively short root hair lengths of all chickpea genotypes (only 0.30–0.46 mm) compared with other plant species; for example, root hair lengths were 0.35–1.19 mm for five perennial pasture grass species grown in three low‐P acid soils (Haling et al ., ) and 0.50–0.75 mm for Dactylis glomerata , Ornithopus spp. and Biserrula pelecinus (Haling et al ., ). The findings of Haling et al .…”
Section: Discussionmentioning
confidence: 97%
“…Root hair length was analysed using the ImageJ program (US National Institute of Health, Bethesda, MA, USA) as described by Haling et al . (), with three randomly selected and homogenously distributed root hairs in each graph measured, giving a total of 15 (3 × 5 photos) root hair lengths per replicate. Specific root length was calculated as root length per unit root DW (Pang et al ., ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Average root hair length was a key component of the Broot hair cylinder volume^which was strongly correlated with plant P uptake in the reports by Waddell et al (2016) and Haling et al (2016). The paper by Vincent et al (2016) reports work to substantially reduce the effort required to quantify root hair development in situ.…”
mentioning
confidence: 94%
“…Similar to Waddell et al (2016), cultivars with greater soil exploration were also found to generally have superior growth and nutrient uptake by Haling et al (2016) and Andresen et al (2016). Andresen et al (2016) examined the root traits, growth and nutrition of several cultivars of onion (Allium cepa L.), spring wheat (Triticum aestivum L.) and lettuce (Lactuca sativa L.) grown in a low nutrient status soil.…”
mentioning
confidence: 99%